The volatility factor and the performance of South African hedge funds - Momoza, Bongiwe (My University, 2017)
The study focuses on determining the driving factors of the performance of different hedge fund strategies in the South African industry. This is done through the application of an augmented capital asset pricing model. The model is predicated on the original (Sharpe, 1964) and (Lintner, 1965) Capital Asset Pricing Model. The researcher uses the excess market returns and the South African Volatility index as independent variables in the explanation of hedge fund returns at strategy and portfolio level. Through the analysis, the researcher finds that the excess market returns and the South African Volatility Index characterize the hedge fund expected returns for some of the strategies using OLS and GMM techniques. The second section uses a system of seemingly unrelated regressions for both the OLS and GMM techniques to determine if the two explanatory variables are priced into the different strategies; this indeed is shown to be the case for some of the strategies examined in the analysis.
Thesis submitted in fulfilment of the requirements for the Masters in Finance and Investments in the Faculty of Commerce, Law and Management Wits Business School At the University of Witwatersrand
Keywords: Stocks--Prices--South Africa; Hedge funds--South Africa; Capital Assets Pricing Model; Finance--Mathematical models